An analytical psychometric function for the dual reference duo-trio (DRDT) method. (March 2022) - Bi, Jian; Lee, Hye-Seong; O'Mahony, Michael
Highlights: An analytical psychometric function for the dual reference duo-trio (DRDT). Two forms of the analytical psychometric function for the DRDT. Tables and R codes for P c, d ', and variance of d ' ( B value) based on the function. Abstract: The dual reference duo-trio (DRDT) is an improved balanced-reference duo-trio method, in which two same references are presented in a test but the reference is changed across the tests. The performance of the DRDT has been investigated theoretically based on a simulation-derived psychometric function in a previous paper published in this journal. The DRDT method is more powerful than the conventional duo-trio and the triangle methods. This paper derives an analytical psychometric function for the DRDT. Another form of the psychometric function for the DRDT is also derived based on the Torgerson's method of triads. Tables and R codes are provided for presentations and calculations of P c, δ (or d ' ), and variance of d ' ( B -value) based on the analytical psychometric function for the method.